PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER MODEL TUTORIAL INTERAKTIF UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI POKOK RELASI DAN FUNGSI - Yudi Jepri Dianta; Ade Putri (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2019)
The background of this research is the lack of a valid, practical and effective ICT-based learning media to learn about relations and functions. This research uses the Research and Development (R&D) method. The development model used in this study is the Plomp instructional model which consists of five phases namely: (1) the initial investigation phase; (2) the design phase; (3) realization phase; (4) test, evaluation and revision phases; (5) implementation phase. The purpose of this study is to develop ICT-based learning media on the subject of relations and functions that are valid, practical and efficient. The subjects of the study were 33 students of VIII grade SMP Negeri 5 Singingi Hilir. The instruments used were validation questionnaire, student response questionnaire and learning motivation questionnaire. Questionnaire sheets were analyzed quantitatively and qualitatively. Based on the results of data analysis, the developed media are in a very valid category, practical to use on learning about relations and functions and effective to increase student learning motivation.